A Review of Virtual Reality Application on STEM Based Education - Ismail I.N.; Zahari N.M.; Hussin M.H.M.; Roslin N.T.; Aziz N.A.; Nurhikmah F.; Abidin S.Z.; Zawawi M.H. (American Institute of Physics, 2025)
The breakthrough of virtual reality technology could benefits humans, especially with the current technological achievement that we have nowadays. Nowadays, people started to use virtual reality more often, especially younger ones. Virtual reality (VR) can serve as an educational tool for students who have limited access to learning material out of their reach. The most common way to implement virtual reality is using the gamification method, in which using games as a way of learning. This article presents an in-depth study of the recent application of virtual reality in STEM-based learning. The study method is by reviewing the application of VR using different ways as its medium of delivery and how it is specifically used. The VR utilization can be done using applications, gamification method, and desktop based. ? 2024 American Institute of Physics Inc.. All rights reserved.